Do subjective assessments of running patterns reflect objective parameters? - Lussiana, T.; Gindre, C.; Mourot, L.; Hebert-Losier, K. (European Journal of Sport Science, 2017)
Running patterns are often categorized into subgroups according to common features before data analysis and interpretation. The Volodalen® method is a simple field-based tool used to classify runners into aerial or terrestrial using a 5-item subjective rating scale. We aimed to validate the Volodalen® method by quantifying the relationship between its subjective scores and 3D biomechanical measures. Fifty-four runners ran 30 s on a treadmill at 10, 12, 14, 16, and 18 km h-1 while their kinematics were assessed subjectively using the Volodalen® method and objectively using 3D motion capture. For each runner and speed, two researchers scored the five Volodalen® items on a 1-to-5 scale, which addressed vertical oscillation, upper-body motion, pelvis and foot position at ground contact, and footstrike pattern. Seven 3D biomechanical parameters reflecting the subjective items were also collected and correlated to the subjective scores. Twenty-eight runners were classified as aerial and 26 as terrestrial. Runner classification did not change with speed, but the relative contribution of the biomechanical parameters to the subjective classification was speed dependent. The magnitude of correlations between subjective and objective measures ranged from trivial to very large. Five of the seven objective parameters significantly differed between aerial and terrestrial runners, and these parameters demonstrated the strongest correlations to the subjective scores. Our results support the validity of the Volodalen® method, whereby the visual appreciation of running gait reflected quantifiable objective parameters. Two minor modifications to the method are proposed to simplify its use and improve agreement between subjective and objective measures.